Alternatif Pembuatan Biodiesel Melalui Transesterifikasi Minyak Castor (Ricinus communis) Menggunakan Katalis Campuran Cangkang Telur Ayam dan Kaolin - Soni Setiadji; Nila Tanyela B; Tety Sudiartati; Eko Prabowo; Bebeh Wahid N (Syarif Hidayatullah State Islamic University, 2017)
Biodiesel was produced by transesterification of castor oil (Ricinus communis) using a catalyst of CaO and kaolin (CaO / kaolin) had been performed. CaO was obtained from the calcination of eggshell. Castor oil is selected as biodiesel feedstock because it belongs to non-food oil and easy to cultivate. In general, the research method aims to comprise the CaO / Kaolin catalysts with a ratio of 15 mmol CaO per 1 gram of kaolin activated using impregnation method and biodiesel produced through transesterification of castor oil using the catalyst at 65 ºC for 8 hours with ratio of castor oil: methanol: catalyst (1: 15: 5% w / w). The reaction is carried out on the reflux system. The XRD analysis show the presence of silica and potassium aluminum silicate hydroxide in the catalyst. The EDS results show the catalyst-forming components CaO and silica. The FTIR analysis results show the absorption peak in the functional group forming the methyl ester compound. Based on the characterization of GC-MS, the largest methyl ester components contained in biodiesel are methyl risinoleate, methyl elaidat, methyl stearate, methyl linoleate, and methyl palmitate. The overall conversion of castor oil to methyl ester using CaO / kaolin catalyst is 97.36%. The largest component in castor oil is risinoleic acid, has been successfully converted to methyl risinoleate by 74.75%.DOI: http://dx.doi.org/10.15408/jkv.v0i0.4778